Strategi Pengelolaan Wisata Pantai Karangjahe Kabupaten Rembang - Abdillah, Rangga Fajar; Bambang, Azis Nur (Environmental Science Program, Ivet University, 2020)
Karangjahe Beach, located in Rembang Regency, Central Java, has a huge tourism potential, this is indicated by the high number of visits per day reaching 2,878 visitors in 2017. The high number of visitors to this natural tourism object in addition to increasing the economy of the surrounding community also threatens sustainability natural resource and the environment in it if it is not managed properly, for that we need a management strategy on this Karangjahe Beach tourism object.SWOT analysis is a method of analysis that can be used to formulate a management strategy for an tourism object by considering the internal and external factors of a tourism object. The results of the strategic formulation of management of the Karangjahe coast natural tourism show that the main priority with the most important weight is to determine the direction of the Karangjahe Beach natural tourism to become sustainable natural tourism. This step was taken because the status of sustainable nature tourism is broader and is likely to be sought by relevant stakeholders. Whereas the strategic step that has the lowest weight rating is the step of making information boards and warning signs.Keywords: Management, Nature Tourism, SWOT, Karangjahe Beach